USED PRINTER DISASSEMBLY PLANNING USING AGGREGATE PLANNING APPROACH AT RCM KOMPUTAMA - Butar Butar, Maulida Boru; Zega, Alva Dika Howuhowu; Gunawan, Mahesa Khalifa (Universitas Gunadarma, 2024)
Indonesia generated an estimated 2 million tons of e-waste. This is expected to increase to 3.2 million tons by 2040. Printers as one of electronic waste (e-waste) can be harmful to the environment, then to reduce the environmental impact of printer disposal and the amount of e-waste that ends up in landfills, printers should be recycled before they are disposed of. This involves disassembling the printer and recycling parts and components. The disassembly process more challenging to plan and execute due to returned product type may vary from product that have been at end-of-life or damaged. Disassembly planning is the first step is to plan the disassembly process, which is important for optimizing the recycling process. Small repair shops are at the forefront of this endeavor, so ensuring their activities run smoothly is of utmost importance. The classic aggregate planning was introduced in disassembly process, considering its capability to coordinate and plan resource to satisfy customers’ demand. The research took place at RCM Komputama, a small printer repair shop in Depok. This research aimed to implement classic aggregate planning in disassembly process, so the repair shop could maximize the number of disassembled units as well as minimize the costs of the disassembly process. After implementing disassembly planning using aggregate planning approach, the processing time needed decreased while satisfying the demands.